2013
DOI: 10.1103/physreva.87.053801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two-beam coupling in strong-field optical pump-probe experiments

Abstract: Nonlinear optics experiments measuring phase shifts induced in a weak probe pulse by a strong pump pulse must account for coherent effects that only occur when the pump and probe pulses are temporally overlapped. It is well known that a weak probe beam experiences a greater phase shift from a strong pump beam than the pump beam induces on itself. The physical mechanism behind the enhanced phase shift is diffraction of pump light into the probe direction by a nonlinear refractive index grating produced by inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 50 publications
(140 reference statements)
0
41
0
Order By: Relevance
“…As an example, extracted 2 n values for the major constituents of air, N 2 and O 2 , show a range of variation exceeding ~100%. Some of this variation can be attributed to nonlinear 3D propagation effects [8,11], unintentional two-beam coupling in degenerate pump-probe experiments owing to the presence of laser-induced Kerr, plasma, and rotational gratings [10,11,13,14], and the laser pulsewidth dependence of the nonlinear response, which had not been directly resolved [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, extracted 2 n values for the major constituents of air, N 2 and O 2 , show a range of variation exceeding ~100%. Some of this variation can be attributed to nonlinear 3D propagation effects [8,11], unintentional two-beam coupling in degenerate pump-probe experiments owing to the presence of laser-induced Kerr, plasma, and rotational gratings [10,11,13,14], and the laser pulsewidth dependence of the nonlinear response, which had not been directly resolved [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…3 (c)]. However, it was recently suggested that the absence of asymmetry could be the result of the the PG effect when considering temporally chirped pulses [42]. Although all our experiments so far were performed for compressed pump and probe beams, a set of data recorded with chirped pump and probe pulses around the region of inversion are compared to numerical simulations in Fig.…”
Section: Chirped Pulsementioning
confidence: 99%
“…The fact that the symmetry of the observed signals is preserved while the pulses are chirped and also that the HOK model does not predict any symmetry reversal of the signal allows to exclude the chirp as a possible artifact from our measurements. Finally, it should be pointed that large chirps, as those responsible for symmetric PG signal [42], lead at constant energy level to a dramatic drop of intensity and consequently to a significant decrease of the birefringence signal above the inversion threshold. This along with a temporal broadening of the signal could have been straightly noticed in the previous studies [1,5] so that any unforeseen significant chirp would have been corrected.…”
Section: Chirped Pulsementioning
confidence: 99%
“…Quite quickly the developed approaches were extended for the description of the interaction of light pulses. The term "two-beam coupling" was still used to define the interaction of pulses (see, e.g., [5][6][7]), but it became often replaced by "pulse energy transfer" [8][9][10][11][12] or "energy exchange" [13]. The researchers dealing with pump-probe techniques were facing the problem of so called "coherent peaks" [14,15], which is a consequence of pump and probe pulse coupling via a dynamic grating, too [16].…”
Section: Introductionmentioning
confidence: 99%